Acoustic behavior of gray whales tagged with biologging devices on foraging grounds - Clayton, Hannah; Cade, David E.; Burnham, Rianna; Calambokidis, John; Goldbogen, Jeremy (Frontiers in Marine Science, 2023)
Understanding the function of baleen whale acoustic signals requires investigation of calling behaviors relative to location, timing, and behavioral state. Previous studies of gray whale (Eschrichtius robustus) vocal behavior have principally used passive recorders and been conducted on breeding grounds and along migratory routes, and not areas associated with foraging. We conducted an analysis of accelerometer and acoustic data collected during 12 deployments of animal-borne tags in 2016, 2019, and 2021 on gray whales that return annually to northern Puget Sound, Washington. We identified 141 calls from gray whales in approximately 128 hours of accelerometer and/or acoustic data collected from tag deployments. Most prominent were pulsive 'rumble-like' calls, upsweeping tones, and moans. Using the tag's accelerometer to identify calls produced by tagged animals enabled us to explore the behavioral context behind call production, revealing that vocalizations were made at slow speeds (mean 1.03 ± 0.26 m s -1 ), shallow depths (mean 7.63 ± 4.99 m), and temporally proximate to surface behavior (mean 43.3 ± 39.66 sec) most similar to non-foraging associated depth (mean 5.78 ±1.46 m) and speed (mean 1.46 ±1.11 m s -1 ) profiles. Vocalizations originating from the tagged animal occurred closer to the conclusion of a foraging event (mean 87.7 ± 119.32 min) than the beginning, with only 7% of these calls occurring during periods of feeding. This study demonstrates that gray whales remain vocal on foraging grounds and that call-associated accelerometry signals can be a valuable tool in identifying individual callers in animal-borne acoustic data.